2009
DOI: 10.1186/1757-1626-2-9373
|View full text |Cite
|
Sign up to set email alerts
|

Role of chemotherapy in the management of primary rectal lymphoma: a case report and review of the literature

Abstract: IntroductionPrimary rectal lymphoma is a rare disease. In this paper we present an unusual case of primary rectal lymphoma which was managed with chemotherapy and discussed by a thorough review of the related literature.Cases presentationAn 85-years-male patient was diagnosed in Sidi Mohammed Ben Abdellah Hospital as having diffuse large B-cell lymphoma of the rectum at a bulky stage two. This patient was managed successfully with 8 treatment cycles of Cyclophosphamide 750 mg/m2 at day 1 of each cycle, Doxorub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…The optimal treatment protocol for PCL is contentious [24,25]. Some authors have suggested systemic chemotherapy alone as the standard treatment, with surgery reserved for complications such as perforation, obstruction, and bleeding [8], whereas others believe that surgery provides better local disease control and improves survival outcome [14,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…The optimal treatment protocol for PCL is contentious [24,25]. Some authors have suggested systemic chemotherapy alone as the standard treatment, with surgery reserved for complications such as perforation, obstruction, and bleeding [8], whereas others believe that surgery provides better local disease control and improves survival outcome [14,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…In our case, colonoscopy showed slough in the rectum, and colonoscopy biopsy revealed a possibly lymphoproliferative lesion (NHL). B cell lymphoma constitutes 85% of all primary colorectal lymphomas, with T cell lymphoma accounting for the remainder (15%) [15]. The differentiation between both lymphomas is done by the use of a cluster of differentiation antibodies (CD).…”
Section: Discussionmentioning
confidence: 99%
“…For tumors not sensitive to chemoradiotherapy, surgery is the first choice. For rectal lymphomas, chemotherapy without surgery can be considered (6)(7)(8)(9)(10)(11).…”
Section: Discussionmentioning
confidence: 99%